PENDIDIKAN LITERASI MEDIA GURU SEKOLAH MIS AL-HIDAYAH DALAM MENGHADAPI PENGARUH NEGATIF DUNIA DIGITAL PADA SISWA - Fadhil Pahlevi Hidayat; Arifin Saleh; Abrar Adhani; Rudianto Rudianto (Universitas Muhammadiyah Tapanuli Selatan, 2021)
In the digital era and current technological developments, there have been changes in human life in various ways, such as communication, especially in obtaining information, so that the negative effects of the digital world cannot be avoided. Therefore, someone needs to have media literacy skills, especially for students so that it can be a tool to reduce the negative influence of the presence of the digital world. Before students can have good media literacy skills, of course, this ability must also be possessed by parents and a teacher. Strengthening literacy skills in a teacher is a very important element because a teacher is a person who will provide learning to students in the world of education. Understanding media literacy is the main foundation in forming a smart and cultured generation in the digital era.